Managing 'Egan' Wheat with a Gene for High Grain Protein. Issue 1 (1st July 2019) - Torrion, Jessica A.; Walsh, Olga S.; Liang, Xi; Bicego, Breno; Sapkota, Anish
Abstract : Core Ideas: No inverse relation existed between grain yield and protein when N > 100 kg ha −1 for Egan. An inverse relationship between grain yield and protein in Egan was only evident at a very low N level. An inverse relationship between Egan grain yield and protein was also evident with year, but grain protein remained at a premium level as long as N > 100 kg ha −1 . Grain yield was limited via reduced productive tillers and grain number on a drought year. Wheat ( Triticum aestivum L.) cultivars with Gpc‐B1 gene are known to achieve high grain protein, which may reduce the N input for achieving high grain yield and quality. Our objectives were to: (i) determine the minimum N input for grain yield and protein in 'Egan' wheat at varying moisture levels and (ii) identify the grain yield‐limiting components for Egan. A study was conducted during 2016–2017 at Creston, MT, on fine sandy loam soil. The experimental design was a strip‐split plot with four replicates. Water regimes of 50% evapotranspiration (50ET), 75% (75ET), 100% (100ET), and rainfed comprised the vertical strips arranged randomly with the horizontal N treatments (control, 168, 224, and 280 kg N ha −1 ). The grain protein, at N > 100 kg ha −1, was stable regardless of yield. An inverse relationship between grain yield and protein was observed only when N was limiting (45 kg ha −1 NO3 –N; 2017 control) where tissue N value is approaching the critical N level (1.8%). Overall, the grain protein also was impacted by environment (year). The yield was mostly influenced by moisture. During 2016 (average year), yield of the deficit treatments was similar to 100ET due to the rainfall events. During 2017 (dry/hot year), yield was reduced with decreasing moisture, which was mostly attributed to the reduced yield sink capacity–reduced productive tiller and grain number at lower moisture levels. Providing the total N does not fall below 100 kg ha −1, yield can be optimized with irrigation with premium protein values.